Chapter La committenza delle comunità e la costruzione degli spazi politici locali: Dronero e la valle Maira (CN) nel Quattrocento - Provero, Luigi (Reti Medievali E-Book, 2021)
Through an analysis of the territory of Dronero and the Maira valley, the essay aims to interpret local political action through a partly unusual key, namely the building commission of the communities. The aim is to highlight the variety of building interventions by communities and to show how these actions are effective keys to interpreting the political dynamics on many different levels: the community economics, the development of collective identity, the manipulation of community and territorial structures, the definition of a ceremonial space, the relations with the lordship. In the Maira valley a community history is outlined, full of tensions and divergent thrusts, between the convergence around the political and ceremonial center of Dronero and the alternative polarities constituted by the numerous settlements scattered in the surrounding basin.